Order reduction of interval systems using alpha and factor division method - Kranthi Kumar D.; Nagar S.K.; Tiwari J.P. (My University, 2025)
The paper proposes a new mixed method for reducing the order of interval systems i.e., systems having uncertain but bounded parameters. The denominator of the reduced order model is obtained by α table and numerator is derived by applying factor division and Cauer second form. A numerical example has been discussed to illustrate the procedures. The errors between the original higher order and reduced order models have also been highlighted to support the effectiveness of the proposed methods. © 2013 Springer.